Learning Curve of Robotic-Assisted Total Knee Arthroplasty for a High-Volume Surgeon - Marchand, Kevin B.; Ehiorobo, Joseph; Mathew, Kevin K.; Marchand, Robert C.; Mont, Michael A. (The Journal of Knee Surgery, 2020)
The learning curve has been established for robotic-assisted total knee arthroplasty (RATKA) during the first month of use; however, there have been no studies evaluating this on a longer term. Therefore, the purpose of this study was to compare operative times for three cohorts during the first year following adoption of RATKA (initial, 6 months, and 1 year) and a prior cohort of manual TKA. We investigated both mean operative times and the variability of operative time in each cohort. This is a learning curve study comparing a single surgeon's experience using RAKTA. The study groups were made up of two cohorts of 60 cementless RATKAs performed at ∼6 months and 1 year of use. A learning curve was created based on the mean operative times and individual operative times were stratified into different cohorts for comparison. Study groups were compared with the surgeon's initial group of 20 cemented RATKAs and 60 cementless manual cases. Descriptive numbers were compiled and mean operative times were compared using Student's t-tests for significant differences with a p-value of < 0.05. The mean surgical times continued to decrease after 6 months of RATKA. In 1 year, the surgeon was performing 88% of the RATKA between 50 and 69 minutes. The initial cohort and 1-year robotic-assisted mean operative times were 81 and 62 minutes, respectively (p < 0.00001). Mean 6-month robotic-assisted operative times were similar to manual times (p = 0.12). A significant lower time was found between the mean operative times for the 1-year robotic-assisted and manual (p = 0.008) TKAs. The data show continued improvement of operative times at 6 months and 1 year when using this new technology. The results of this study are important because they demonstrate how the complexity of a technology which initially increases operative time can be overcome and become more time-effective than conventional techniques.
Keywords: learning curve; robotic-assisted total knee arthroplasty; knee; osteoarthritis